Use of Ex-Vivo Lung Perfusion for Planned Left Single-Lung Transplant - Aravind Krishnan, MD; Elbert Heng, MD; Chawannuch Ruaengsri, MD; Amit Banga, MD; Brandon A. Guenthart, MD; Y. Joseph Woo, MD; John Ward MacArthur, MD (Annals of Thoracic Surgery Short Reports)
The donor shortage in lung transplantation is further exacerbated by the highest organ turn-down rate among all solid organ transplants. Here we present a case of planned single-lung ex-vivo lung perfusion that enabled the use of a single lung for transplantation, that otherwise may have gone unallocated. Creative management of the donor trachea enabled use of both the left and right lungs for separate recipients. Techniques like this may inspire confidence in expansion in use of ex-vivo lung perfusion and a commensurate increase in donor organ utilization for lung transplantation.